2016
DOI: 10.1155/2016/6491049
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Clinical Characteristics of Patients with Primary Duodenal Adenocarcinoma: A Single-Center Experience from China

Abstract: Aim. To evaluate the clinical risk factors influencing overall survival of patients with duodenal adenocarcinoma after potentially curative resection. Methods. A series of 201 patients with primary duodenal adenocarcinoma who underwent surgery from 1999 to 2014 at Chinese Medical Academic Cancer Hospital were studied by retrospective chart review and subsequent telephone follow-up. Results. Resectional surgery was performed in 138 of the 201 patients to attempt curative treatment, while 63 patients were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 20 publications
1
36
0
4
Order By: Relevance
“…2 b). 12 , 31 , 32 , 34 , 36 , 37 , 41 , 42 , 44 46 Lymph node involvement remained an independent prognostic factor in most studies after correction for other clinicopathological factors, including tumor size, differentiation grade, and disease stage. 12 , 24 , 31 , 34 , 37 , 41 , 42 , 45 , 46 …”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…2 b). 12 , 31 , 32 , 34 , 36 , 37 , 41 , 42 , 44 46 Lymph node involvement remained an independent prognostic factor in most studies after correction for other clinicopathological factors, including tumor size, differentiation grade, and disease stage. 12 , 24 , 31 , 34 , 37 , 41 , 42 , 45 , 46 …”
Section: Resultsmentioning
confidence: 97%
“…A total of eight studies, comparing survival of patients treated with either pancreaticoduodenectomy or segmental resection, were eligible for comparison. 10 12 , 22 , 32 , 34 , 39 , 43 All these studies reported no significant differences in survival comparing segmental resection with pancreaticoduodenectomy. Two studies reported a greater number of lymph nodes sampled and more positive lymph nodes removed in patients undergoing pancreaticoduodenectomy, compared with segmental resection.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Qing-Long Jiang et al . revealed that LN metastasis and vascular invasion were independent prognostic factors that were negatively associated with survival in patients undergoing curative resection 21 . In this study, through univariable analysis and subsequent multivariable Cox regression analysis, we identified patients with elder age, worse tumor grade and advanced TNM stage had shorter CSS.…”
Section: Discussionmentioning
confidence: 96%
“…The median overall survival(OS) of metastatic duodenum adenocarcinoma, ranging from 2 to 8 months, is much worse than advanced colorectal cancer 4 . Various studies have attempted to evaluate different prognostic factors for primary duodenum adenocarcinoma, and some studies have identified the T stage, nodal metastasis, pathologic grade, lymphovascular invasion, age, weight loss and perineural invasion as prognostic factors 5 - 12 . Due to the rare incidence, the number of patients in previous studies was relatively small, with a range from 17 to 178 patients 5 - 12 .…”
Section: Introductionmentioning
confidence: 99%